Three new species of Scottmoria (Lecythidaceae) from northwestern South America - Cornejo, Xavier; Prance, Ghillean T. (Phytotaxa, 2024)
Three new species of Neotropical Lecythidaceae are formally described: Scottmoria albomarginata from western Ecuador, S. decurrens from northwestern Ecuador to western Colombia, and S. spiralocucullata from western Amazonia in eastern Ecuador to the westernmost state of Acre in Brazil. The new species are illustrated and the relationships with related species are discussed.